Efikasi diri, kepuasan kerja, pengembangan karir dan perilaku kewargaan organisasional pada guru - Dwi Wiryanti; Miguna Astuti; Iwan Kresna Setiadi; Acim Heri Iswanto (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
This quantitative study aims to determine the effect of self-efficacy, job satisfaction, and career development on organizational citizenship behavior (OCB) for teachers in the city of Depok, West Java, Indonesia. Data was collected using an online questionnaire of 95 respondents with a purposive approach. The analysis technique used is the PLS (Partial Least Square) analysis method. The results of this study indicate that self-efficacy has no significant effect on OCB, while job satisfaction and career development have affected OCB. This study provides insight into efforts to improve OCB among teachers in Indonesia.